GrTCP11, a Cotton TCP Transcription Factor, Inhibits Root Hair Elongation by Down-Regulating Jasmonic Acid Pathway in Arabidopsis thaliana - Hao, Juan; Lou, Panpan; Han, Yidie; Chen, Zhehao; Chen, Jianmei; Ni, Jun; Yang, Yanjun; Jiang, Zhifang; Xu, Maojun (Frontiers in Plant Science, 2021)
TCP transcription factors play important roles in diverse aspects of plant development as transcriptional activators or repressors. However, the functional mechanisms of TCPs are not well understood, especially in cotton fibers. Here, we identified a total of 37 non-redundant TCP proteins from the diploid cotton (Gossypium raimondii), which showed great diversity in the expression profile. GrTCP11, an ortholog of AtTCP11, was preferentially expressed in cotton anthers and during fiber initiation and secondary cell wall synthesis stages. Overexpression of GrTCP11 in Arabidopsis thaliana reduced root hair length and delayed flowering. It was found that GrTCP11 negatively regulated genes involved in jasmonic acid (JA) biosynthesis and response, such as AtLOX4, AtAOS, AtAOC1, AtAOC3, AtJAZ1, AtJAZ2, AtMYC2 and AtERF1, which resulted in a decrease in JA concentration in the overexpressed transgenic lines. As with the JA-deficient mutant dde2-2, the transgenic line 4-1 was insensitive to 50 μM methyl jasmonate, compared with the wild-type plants. The results suggest that GrTCP11 may be an important transcription factor for cotton fiber development, by negatively regulating JA biosynthesis and response.